Conservation of Epstein-Barr Virus Cytotoxic T-Cell Epitopes in Posttransplant Lymphomas : Implications for Immune Therapy - Tao, Qian (American Society for Investigative Pathology, 2002)
Posttransplant lymphoproliferative disease can be treated by the infusion of Epstein-Barr virus-specific cytotoxic T lymphocytes, which were raised against lymphocytes immortalized with a laboratory strain of Epstein-Barr virus (B95.8). Whether the immunodominant epitopes in B95.8 are shared in virus from tumors will affect the general applicability of this therapy. We have characterized the viral strain and the sequence of commonly recognized cytotoxic T-lymphocyte epitopes in 25 posttransplant lymphoproliferative disease specimens from 19 patients. Type A virus was present in 24 of 25 specimens. No variation in two LMP2A epitopes and a few variations mostly outside the targeted epitopes or silent in three EBNA3C epitopes were found, with one variation (Arg to Lys) detected in an EBNA3C epitope in 12 of 24 tumors. However, cytotoxic T lymphocytes to B95-8-derived EBNA3C peptides specifically lysed both B95-8 and the Lys-variant peptide-loaded target cells, although with less efficiency. These results suggest that adoptive immunotherapy using cytotoxic T lymphocytes expanded with B95.8 stimulators or vaccine strategies using B95.8-derived sequence will generally target Epstein-Barr virus strains present in posttransplant lymphoproliferative disease tumors.